HIGH TEMPERATURE MECHANICAL PROPERTIES OF Al-Al4C3 COMPOSITE PRODUCED BY MECHANICAL ALLOYING - Michal Besterci; Ferdinand Dobeš; Tibor Kvačkaj; Katarína Sülleiová; Beata Ballóková; Oksana Velgosová (Acta Metallurgica Slovaca, 2014)
A method of mechanical alloying process is described. It was proved that the transformation efficiency of carbon to Al4C3 by heat treatment of aluminium with the porous furnace black and electrographite at temperatures 723 – 873 K and time periods 1 - 10 hours is higher than that of the hard cracked graphite. The size of Al4C3 dispersed phase was measured on thin foil and it was constant and as small as 30 nm. Subgrain size measured in the range of 100 grains in thin foils depended on the carbon type.. It ranged from 0.3 to 0.7 μm. Mechanical properties were analyzed in a microstructural matrix (after extrusion) as well as in nano-matrix The temperature dependence of ductility, and reduction of area in the temperature range of 623 – 723 K and strain rate of 10-1 s-1, indicated a considerable increase of properties. In a case when the volume fraction of Al4C3 changes from lower to higher, the grain rotation mechanism dominates instead of the grain boundary sliding. Creep parameters for Al-Al4C3 systems and commercial IN9021 and IN9052 systems were compared. The dependence of the minimum deflection rate on the applied force as well as the dependence of the time to fracture on the applied force for two temperature levels (623 and 723 K) by small punch testing is depicted. The anisotropy of the creep properties and fracture using small punch tests for the Al-Al4C3 system produced by ECAP were analyzed.